STRUCTURAL TRANSFORMATIONS OF THE RUSSIAN OIL AND GAS COMPLEX: THE STRATEGIC ASPECT - Plenkina, Vera; Volynskaya, Natalia; Lenkova, Olga (Revista Inclusiones, 2020)
The article provides an overview of the key issues engaged in the draft Energy Strategy of the Russian Federation up to 2035. The authors of the present article describe main directions of the structural transformation of the Russian oil and gas complex in the context of its individual segments (exploration and production, processing, and export) which are already being implemented, as well as analyze prospective transformations planned for implementation in the projection period. An assessment is made and a conclusion is drawn about the inconsistency of individual tasks identified in the Energy Strategy. The threats and opportunities contained in the challenges (trends) of the external environment are described in the format of the strategic balance matrix. The authors discuss possible trajectories of further development of the oil and gas sector and their adjustments from the standpoint of the strategic management theory and give comments on the prospects and opportunities of using certain measures reflected in the Energy Strategy of Russia.